2017
DOI: 10.1055/s-0037-1615817
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Use of Aspirin in the Prevention of Deep Vein Thrombosis in Major Elective Lower Limb Orthopedic Surgery: An Update from the Past 3 Years

Abstract: Introduction  Currently there are no consensuses in the national guidance on thromboprophylaxis following major elective lower limb surgery. Emerging clinical evidence suggests that aspirin could be just as effective as anticoagulants with a lower cost. The aim of this study was to provide an update based on literature of the past 3 years for the use of aspirin as thromboprophylaxis after knee and hip arthroplasty. Materials and Methods  MEDLINE/EMBASE search was performed with appropriate terms for original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…However, bleeding risk varies dramatically among heparin and direct oral anticoagulants, potentially suggesting additional etiopathogenic factors. In people, anticoagulants are associated with similar or higher rates of adverse events than antiplatelet drugs . The incidence of gastrointestinal bleeding in dogs administered anticoagulants is unknown, and results of this study should not be extrapolated to their use.…”
Section: Discussionmentioning
confidence: 90%
“…However, bleeding risk varies dramatically among heparin and direct oral anticoagulants, potentially suggesting additional etiopathogenic factors. In people, anticoagulants are associated with similar or higher rates of adverse events than antiplatelet drugs . The incidence of gastrointestinal bleeding in dogs administered anticoagulants is unknown, and results of this study should not be extrapolated to their use.…”
Section: Discussionmentioning
confidence: 90%
“…Platelets are recruited to the venous wall shortly after blood flow restriction and play an important role in DVT as platelet depletion substantially reduces thrombosis [28] . A role of platelets in DVT is supported by the observations that an antiplatelet drug aspirin reduces DVT in mice (by preventing thromboxane A2 synthesis) [82] and VTE in patients undergoing orthopedic surgery 83 , 84 ; a condition frequently associated with compromised venous blood flow. Importantly, efficacy of venous thrombosis prophylaxis by aspirin is non-inferior to that of rivaroxaban, an anticoagulant widely used in clinical practice [85] , which confirms involvement of platelets in DVT pathogenesis.…”
Section: Stage 3: Blood Cell Recruitmentmentioning
confidence: 98%
“…Furthermore, platelets recruited to the venous wall may release high-mobility group box 1 (HMGB1) that can induce NETosis (formation of neutrophil extracellular traps), resulting in a scaffold for adhering platelets and red blood cells and promoting thrombin generation and fibrin deposition [190][191][192]. Not surprisingly, recent studies found that aspirin reduces DVT in mice and VTE in patients undergoing orthopedic surgery [193][194][195].…”
Section: Thrombosis and The Interplay Between Platelets And Coagulationmentioning
confidence: 99%